Application of enhanced recovery after surgery in the perioperative nursing of elderly patients undergoing hip replacement (加速康复外科理念在老年髋关节置换术围手术期护理中的应用) - XIN Lan (信岚); TANG Bi (唐碧); CHEN Mingying (陈明英) (中西医结合护理)
Objective To explore the effect of enhanced recovery after surgery (ERAS) in the perioperative nursing of elderly patients undergoing hip replacement. Methods Totally 58 elderly patients undergoing hip replacement were randomly divided into the observation group and the control group, with 29 cases in each group. The control group received routine care during the period of operation, while the observation group received perioperative nursing based on ERAS. The Activity of Daily Living (ADL), Harris Hip Score (HHS), Visual Analogue Pain Score (VAS) and were observed before intervention, 1 day, 1 week and 2 weeks after intervention, and the off-bed time was recorded. Results The ADL score and HSS score were significantly increased in both two groups at 2 weeks after intervention(P＜0. 05), and the VAS Score was decreased significantly at 2 weeks after intervention(P＜0. 05). Patients in the observation group achieved higher ADL score, higher HSS score and lower VAS score at 2 weeks after intervention compared with those in the control group (P＜0. 05) . T he off-bed time was (9. 45±2. 53) d in the observation group, which was shorter than (13. 83±3. 91) d in the control group (P＜0. 05). Conclusion The perioperative nursing based on ERAS is effective to reduce the postoperative pain of elderly patients undergoing hip replacement, and improve their activity of daily living. (目的 探讨加速康复外科(ERAS)理念在老年髋关节置换术围手术期护理中的应用效果。方法 58例行髋关节置换术的患者随机分为观察组和对照组, 各29例。对照组给予常规围手术期护理, 观察组基于ERAS理念开展围手术期护理。观察2组干预前、干预后1天、干预后1周以及干预后2周时的自理能力、髋关节功能以及疼痛程度。记录2组术后下床活动的时间。结论 干预后2周时, 2组日常生活活动能力量表(ADL)、髋关节功能评分(HSS)升高, 疼痛视觉模拟评分量表(VAS)评分降低, 与干预前比较, 差异有统计学意义(P＜0. 05); 干预后2周时观察组ADL、HSS评分高于对照组, VAS评分低于对照组, 差异有统计学意义(P＜0. 05)。观察组患者下床活动时间为术后(9. 45±2. 53) d, 短于对照组(13. 83±3. 91) d, 差异有统计学意义(P＜0. 05)。结论 基于ERAS理念开展老年髋关节置换术围手术期护理, 能有效缓解患者的疼痛, 提高日常生活自理的能力, 加快康复。)